Usefulness of meiofauna at high taxonomic levels as a tool to assess harbor quality status. Marina del Este Harbor (Granada, Spain) as a case study - Sedano, Francisco (2014)
Meiofaunal communities from a harbor with low levels of disturbance (Marina del Este Harbor) and a control area (Galera Beach) at the subtropical coast of Almuñecar (Spain) were compared to evaluate the usefulness of meiofauna as a tool for environmental monitoring at high taxonomic levels in harbors. Three sites were sampled at the control area with different granulometries (Fine, Medium and Coarse). A mixture of fine and medium sands were found in the Medium granulometry site, which had the same granulometric composition as the Harbor Site. Al, Ba, Ca, Mg, Mn and Ni concentrations at the harbor site were twice as high as those found in the Medium Control Site, which correlates with the highest organic content. Results of the one-way ANOVA and the multivariate analysis showed significant differences regarding the meiofauna abundancebetween the Medium and Harbor Sites. In conclusion, the study of meiofaunal communities at high taxonomic levels can detect low levels of disturbance in harbors, which makes it a useful tool for preliminary assessment of environmental quality and, therefore, can be implemented in management policies.